2011
DOI: 10.1111/j.1745-7599.2011.00601.x
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring new nurse practitioners to accelerate their development as primary care providers: A literature review

Abstract: A mentoring program for new NPs working in primary care could accelerate productivity, increase job satisfaction, and provide longevity in the primary care setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 31 publications
0
47
0
Order By: Relevance
“…There is empiric evidence for the importance of mentorship during the NP transition to practice (Harrington, 2011;Hayes, 1998Hayes, , 2001Hill & Sawatzky, 2011), but limited information regarding successful mentoring programs and successful mentoring of NP students (Poronsky, 2012). Mentorship by a colleague (SullivanBentz et al, 2010), and a formal orientation program (Bahouth & Esposito-Herr, 2009;Barnes, 2015;Cleary, Matheson, & Happell, 2009;Cusson & Strange, 2008, Flinter, 2012 have been associated with improved NP role transition, but more information is needed on the ideal structure and content of successful mentoring and mentorship programs (Poronsky, 2012).…”
Section: Prior Work Experiencementioning
confidence: 99%
“…There is empiric evidence for the importance of mentorship during the NP transition to practice (Harrington, 2011;Hayes, 1998Hayes, , 2001Hill & Sawatzky, 2011), but limited information regarding successful mentoring programs and successful mentoring of NP students (Poronsky, 2012). Mentorship by a colleague (SullivanBentz et al, 2010), and a formal orientation program (Bahouth & Esposito-Herr, 2009;Barnes, 2015;Cleary, Matheson, & Happell, 2009;Cusson & Strange, 2008, Flinter, 2012 have been associated with improved NP role transition, but more information is needed on the ideal structure and content of successful mentoring and mentorship programs (Poronsky, 2012).…”
Section: Prior Work Experiencementioning
confidence: 99%
“…One key area identifi ed as benefi ting from mentoring relationships is employee productivity. In a review of the health care literature, benefi ts and positive outcomes of mentoring programs were identifi ed, and the potential for such relationships enhancing workforce capabilities and competencies was recognized (Harrington, 2011). One such program value resulting from the development of an effective mentoring relationship is increased employee productivity and job satisfaction in practice (Brown & Olshansky, 1997;Butler, 1989).…”
Section: Background/literature Reviewmentioning
confidence: 99%
“…The Patient Protection and Affordable Care Act of 2010 will provide access to primary care for 32 million Americans who were previously uninsured, resulting in an expected shortage of more than 45,000 primary care physicians (Kirch, 2012;Poghosyan, Lucero, Rauch, & Bekowitz, 2012). In addition, the U.S. population is aging, with nearly 78 million baby boomers at or nearing retirement (Bodenheimer & Pham, 2010;Harrington, 2011;Poghosyan et al, 2012). Clearly, primary care must be restructured to provide high-quality, cost-effective care (Poghosyan et al, 2012).…”
mentioning
confidence: 96%
“…Several studies have compared the health outcomes of patients receiving care from NPs versus physicians, and most have concluded that NPs provide comparable care and often surpass physicians in quality of care (Miller, Snyder, & Lindeke, 2005). However, despite rigorous NP educational programs, surveys have indicated that many new graduates feel unprepared for practice (Hart & Macnee, 2007;Rosenzweig, Giblin, Morse, Sheehy, & Sommer, 2012;Sullivan-Bentz et al, 2010), and the literature lacks data addressing the professional development and mentorship needs of novice and veteran NPs (Barker, 2006;Doerksen, 2010;Harrington, 2011). The purpose of this quantitative descriptive study was to assess the professional development and mentorship needs of new and experienced NPs as a first step toward development of effective NP professional development programs.…”
mentioning
confidence: 97%